2016
DOI: 10.1186/s13023-016-0495-y
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the clinical spectrum of COL1A1 mutations in different forms of glaucoma

Abstract: BackgroundPrimary congenital glaucoma (PCG) and early onset glaucomas are one of the major causes of children and young adult blindness worldwide. Both autosomal recessive and dominant inheritance have been described with involvement of several genes including CYP1B1, FOXC1, PITX2, MYOC and PAX6. However, mutations in these genes explain only a small fraction of cases suggesting the presence of further candidate genes.MethodsTo elucidate further genetic causes of these conditions whole exome sequencing (WES) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 48 publications
(49 reference statements)
0
23
0
Order By: Relevance
“…As reasoned in Buie et al 67 , besides provoking an increase in calcification 68 , 69 , BMP2 could influence IOP by its consequent increases in Col1A1 67 , a trabecular meshwork ECM component, originally reported to be enhanced under glaucomatous conditions 70 . More recently Col1A1 has been found to be genetically linked to glaucoma cohorts 71 . In the same Buie’s paper 67 , it was also discussed the well-known crosstalk between BMP2 and the Wnt/β-catenin pathways and the activation of each of the pathways by the other 72 , 73 .…”
Section: Discussionmentioning
confidence: 99%
“…As reasoned in Buie et al 67 , besides provoking an increase in calcification 68 , 69 , BMP2 could influence IOP by its consequent increases in Col1A1 67 , a trabecular meshwork ECM component, originally reported to be enhanced under glaucomatous conditions 70 . More recently Col1A1 has been found to be genetically linked to glaucoma cohorts 71 . In the same Buie’s paper 67 , it was also discussed the well-known crosstalk between BMP2 and the Wnt/β-catenin pathways and the activation of each of the pathways by the other 72 , 73 .…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in the COL1A1 gene are typically associated with skeletal and dermatological conditions, including Ehlers-Danlos syndrome, bone mineral density variation, osteoporosis and Caffey disease ( 90 ). Mauri et al ( 91 ) identified compound heterozygous variants of COL1A1 (p.Met264Leu; p.Ala1083Thr) in 26 patients with PCG by whole-exome sequencing. Collagen protein is a core component of the extracellular matrix (ECM) of the TM, SC and lamina cribrosa, all of which are ocular tissues involved in the development of glaucoma.…”
Section: Genetic Aspects and Mutations In Genes Associated With Pcmentioning
confidence: 99%
“…MYOC is detected in the aqueous humor and MYOC mutations are the most common type of mutation in patients with glaucoma (10), accounting for 10% of juvenile-onset open-angle glaucoma (JOAG) (11) and 2-4% of adult-onset POAG (12). JOAG, unlike adult-onset POAG, has a close genotype-phenotype association with regard to myocilin mutations and glaucoma, and typical signs include high intra-ocular pressure (IOP) (13,14), severe optic nerve damage and earlier age at onset (usually <40 years) (15,16), which, if left untreated, results in severe visual impairment (17).…”
Section: Introductionmentioning
confidence: 99%